THE MAKING OF INSTRUCTIONAL VIDEOS FOR STUDENTS OF BASIC GRAMMAR CLASSES IN VOCATIONAL COLLEGE UGM - Andri Handayani; Wahyu Kartika Wienanda; Alfelia Nugky Permatasari (STKIP PGRI Tulungagung, 2019)
Some concepts in English grammar usually confuse students such as the use of articles and tenses. More interesting learning methods such as flipped class and e-learning using video are needed to improve students’ understanding about English grammar. The purpose of this paper is to convey the making process of instructional video for students of Basic Grammar Classes of the English Program, Vocational College, Universitas Gadjah Mada. There are two instructional videos made consisting of two topics; quantifiers and forms of others. The making process was from June to September 2018. The results show that the making process of instructional videos includes video content preparation, shooting process and editing. Video content making includes compiling materials, writing script and arranging storyboard. Meanwhile the shooting and editing processes were handled by a professional video maker. The constraints faced during the shooting process were the difficulty to act naturally and to remember the lines also problem of sound noise. The use of animation also becomes constraint in editing process since more time and energy were consumed to finish the video.